KEPEMIMPINAN DOSEN PENDIDIKAN ISLAM PADA ERA REVOLUSI INDUSTRI 4.0 - Trinova, Zulvia; Syam, Aminuddin; Nini, Nini (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2020)
The very fast growth of the era requires mental readiness to face the dynamics of the industrial revolution era 4.0. Lecturers of Islamic Education, in addition to being educators and teachers as well as leaders. For this reason, a lecturer in Islamic Education who understands his role is needed so that he can carry out his leadership function optimally in the era of the industrial revolution 4.0. This library research was conducted by examining various literatures and analyzes regarding the leadership of Islamic education lecturers in the era of the industrial revolution 4.0. The data collection technique was carried out by analyzing various available sources on leadership for Islamic Education lecturers in the era of the industrial revolution 4.0. The lecturer of Islamic Education as a leader puts forward a work ethic in leading based on a calling, leading with willpower, leading sincerely, leading thoroughly, leading creatively, leading excellently. Lecturers of Islamic Education have roles as role models, inspirers, agents of change, developers of Islamic culture in the era of the industrial revolution 4.0. All parties need to work together to improve the quality of learning in facing the threats and challenges in the era of the industrial revolution 4.0 optimally.